Influence of Drought and Sowing Time on Protein Composition, Antinutrients, and Mineral Contents of Wheat. (2nd May 2012) - Singh, Sondeep; Gupta, Anil K.; Kaur, Narinder
Abstract : The present study in a two-year experiment investigated the influence of drought and sowing time on protein composition, antinutrients, and mineral contents of wheat whole meal of two genotypes differing in their water requirements. Different thermal conditions prevailing during the grain filling period under different sowing time generated a large effect on the amount of total soluble proteins. Late sown conditions offered higher protein content accompanied by increased albumin-globulin but decreased glutenin content. Fe content was increased to 20–23%; however, tannin decreased to 18–35% under early sown rain-fed conditions as compared to irrigated timely sown conditions in both the genotypes. Activity of trypsin inhibitor was decreased under rain-fed conditions in both genotypes. This study inferred that variable sowing times and irrigation practices can be used for inducing variation in different wheat whole meal quality characteristics. Lower temperature prevailing under early sown rain-fed conditions; resulted in higher protein content. Higher Fe and lower tannin contents were reported under early sown rain-fed conditions however, late sown conditions offered an increase in phytic acid accompanied by decreased micronutrients and glutenin contents.